Regulation and functional diversification of root hairs. (November 2018) - Cui, Songkui; Suzaki, Takuya; Tominaga-Wada, Rumi; Yoshida, Satoko
Abstract: Root hairs result from the polar outgrowth of root epidermis cells in vascular plants. Root hair development processes are regulated by intrinsic genetic programs, which are flexibly modulated by environmental conditions, such as nutrient availability. Basic programs for root hair development were present in early land plants. Subsequently, some plants developed the ability to utilize root hairs for specific functions, in particular, for interactions with other organisms, such as legume-rhizobia and host plants-parasites interactions. In this review, we summarize the molecular regulation of root hair development and the modulation of root hairs under limited nutrient supply and during interactions with other organisms.